The essence of the communicative interpersonal conflict according to the sociolinguistic survey (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
The article analyses the results of a sociolinguistic survey conducted with the aim of distinguishing and differentiating the means of language, Ukrainian skills accomplish this in the conflicting communication with different opponents.The questions of the questionnaire belong to two blocks. The first contains language tools that allow us to identify communicative reactions of informants during an interpersonal conflict with relative (informal) opponents; in the second one – with a stranger (a friend or a stranger) as an opponent. The elements of the representation of conflict communication are selected the same for both blocks (35 markers). These are lexical markers of the semantic-thematic groups: “assessment of personality traits of the opponent” (substantives, attributes), “assessment of the process of conflict development”. Also, the phraseological markers of the semantic-thematic group “subject’s actions in the conflict” are described. The survey found that lexical markers representing the reaction to a relative opponent predominating when respondents avoid words that are specific markers, their semantics indicates a person's defects or words are called an acquired deficiency of the individual, which is difficult or impossible to remove. Regarding the non-relative opponent, the informants believe that it is not desirable to use markers of a general assessment, which represent the lack of specificity of the impression of the opponent, or those that call the natural features of the person.According to the questionnaire, stylistically marked and unmarked signs of the language cause conflicting communication. However, the respondents understand the semantic-stylistic peculiarity of the marked words and phraseological units. Therefore they are avoiding words with a fixed functional and stylistic component of the connotation, which complicate communication with a relative opponent. Under these conditions, they prefer stylistically unmarked elements. In communicating with non-relative opponents, informants do not restrict themselves in conflicting reactions, preferring the stylistically marked units of language. However, respondents consider the public experience. Therefore, they demonstrate their desire to follow Ukrainian linguistic and cultural rules. Their legislative regulators of communicative conflict behaviour are stable, and respondents prefer the way to avoid conflicts.
Keywords: sociolinguistic questioning; conflict communication; stylistically labelled and unmarked signs of language; oral culture